TEAD4 Transcriptionally Activates TRIB3 to Induce Ferroptosis Resistance through the MEK/ERK Signaling Pathway in Colorectal Cancer - Jianguo Wang; Xiangbo Wu (Gut and Liver)
Background/Aims : Colorectal cancer (CRC) is the third most prevalent malignancy and the second leading cause of cancer-associated death worldwide. Ferroptosis is a form of regulated cell death that has been linked to the treatment of CRC. Tribbles homolog 3 (TRIB3) and TEA domain transcription factor (TEAD4) are linked with the progression of various cancers, but their role in ferroptosis remains unclear. Methods : We analyzed TRIB3 and TEAD4 expression in CRC tissues using bioinformatics and examined the TRIB3-ferroptosis association. Immunohistochemistry was employed to determine the expression levels of TRIB3 and glutathione peroxidase 4 (GPX4). Real-time quantitative polymerase chain reaction was utilized to measure the mRNA levels of TRIB3 and TEAD4. Western blot was performed to assess the changes in the levels of proteins related to ferroptosis and MEK/ERK pathway. Dual luciferase assays and chromatin immunoprecipitation assays were employed to detect TEAD4TRIB3-TEAD4 targeting. We also employed colony formation assays to analyze cell proliferation, flow cytometry to measure reactive oxygen species levels, and detection kits to measure Fe2 +, glutathione and NADPH levels. Results : TRIB3 was upregulated in CRC cells and tissues and was implicated in the ferroptosis pathway, demonstrating a positive association with GPX4. TRIB3 positively modulated ferroptosis proteins and the MEK/ERK signaling pathway, increasing the ferroptosis resistance of CRC cells. Overexpression of TRIB3 in TEAD4-knockdown cells significantly increased the ferroptosis resistance of CRC cells. Conclusions : TEAD4 increases the expression level of TRIB3 through transcriptional activation, thereby controlling the MEK/ERK signaling pathway and inducing ferroptosis resistance in CRC cells.